Adsorption of Co(II) from aqueous solution using municipal sludge biochar modified by HNO3 - Chunlian Hu (IWA Publishing, 2021)
Here adsorption studies were proposed on a carboxylated sludge biochar (CSB) material modified by HNO3 to assess its capacity in the removal of cobalt from aqueous solution. The as-prepared sludge biochar material was characterized by Brunauer-Emmett-Teller (BET) analysis, Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), energy-dispersive spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). The isotherm process could be well described by the Langmuir isotherm model. The adsorption kinetics indicated that cobalt adsorption followed a pseudo-second-order kinetics model. The mechanism between Co(II) and biochar involved electrostatic interaction, ion exchange, surface complexation and physical function. The adsorption capacity on CSB was as high as 72.27 mg·g−1, surpassing original sludge biochar (SB) as CSB had abundant oxygen-containing functional groups and many hydroxyls, plus the BET surface areas increased when SB was modified by HNO3, which stimulated adsorption effect. Therefore, this work shows that CSB could be used as an efficient adsorbent to remove Co(II) in wastewater. Highlights The material has abundant oxygen-containing functional groups, which are beneficial for binding Co(II).; The isotherm process could be well described by the Langmuir isotherm model and pseudo-second-order kinetic model.; The adsorbent has an efficient adsorption capacity for Co(II), as high as 72.27 mg·g−1.;